The divergence of learning analytics research - Khuzairi N.M.S.; Cob Z.C. (Science and Engineering Research Support Society, 2023)
This study represents a review of Learning Analytics journals with the goal to examine reported research objectives, educational data collected and the intended end-user of the corresponding analysed data proposed by all current studies available in relevant databases. A total of 62 research articles were selected from an initial accumulation of 373 papers for this review. The findings present a clear divergence of Learning Analytics research into distinct subsets and it is revealed that the term Learning Analytics is labelled indiscriminately. We then show how a categorization of research subsets will prompt a reduction of term sprawl and also to avert confusion in the current education research environment. With this key points above we offer an approach to classify future Learning Analytics research into three specific subsets (student-centric, teacher-centric and institution-centric) based on identifiable criteria with the goal of fostering new avenues for future ground breaking research works in education. 2020 SERSC.